IDENTIFIKASI FAKTOR RISIKO KEJADIAN LOW BACK PAIN PADA PEKERJA INDUSTRI KATERING - Zakky, Dandy; Lufthansyahrizal, Fauzi; Yudhawati, Donna Dwi (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2023)
Background: Low back pain is pain that is felt in the affected anatomical area with various variations in the duration of pain. This pain is felt in the lumbar or lumbo-sacral region. Occupational diseases caused by non-ergonomic conditions include musculoskeletal disorders. Food industry workers are at risk of low back pain due to their activities such as bending, lifting and carrying heavy loads for a long time and repetitively. The purpose of this systematic review is to determine the relationship of position and length of work of ketring business workers to the incidence of LBP. Methods: searches are conducted through Google Scholars, PubMed, Cochrane Library, ResearchGate and Science Direct. Obtained 30 journals that contain the topic of low back pain in catering industry workers. Results: from 30 journals, 12 cross-sectional studies, 7 systematic Reviews, 4 literature reviews, 5 cohort studies, 1 meta-analysis, and 1 case-control study were obtained. Discussion: LBP occurs due to the biomechanics of the lumbar vertebrae due to changes in body weight points with compensation for changes in body position and will cause pain. Muscle strain and spinal ligament sprain are among the main causes of LBP. lifting positions that are less ergonomic and repetitive in the long term are causing complaints of low back pain in ketring workers. Conclusion: the risk factors for low back Pain (LBP) in workers in the mining industry are caused by several factors such as position and posture when working which tend to be static and repetitive, old age workers, workers with excess weight. Keywords: Risk factor, LBP, worker, kitchen, catering